PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA TEMA SELALU BERHEMAT ENERGI SUBTEMA MANFAAT ENERGI SISWA KELAS IV DI SD - Anggraini, Silvy; Destiniar, Destiniar; Farhan Yadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine whether the Make a Match learning model affects the learning outcomes of fourth-grade elementary school students on the theme of energy conservation, specifically the sub-theme of energy benefits, or not. There are two hypotheses in this study: the application of the Make a Match model affects the learning outcomes of fourth-grade students on the theme of energy conservation, specifically the sub-theme of energy benefits (H_a), and the application of the Make a Match learning model does not affect the learning outcomes of fourth-grade students on the theme of energy conservation, specifically the sub-theme of energy benefits (H_0). The research method used is an experimental method with a One Group Pretest-Posttest Design. The population of this study consists of all fourth-grade elementary school students, totaling 25 students. Since the population is less than 25, the entire population is used as the sample in this study. Data collection was conducted through testing and interviews. The research data were analyzed using descriptive analysis and prerequisite analysis tests. Based on the data analysis, it is known that the Significance (2-tailed) value is 0.000, while the significance level is 0.05. Therefore, it can be concluded that the Make a Match learning model affects the learning outcomes of fourth-grade students on the theme of energy conservation, specifically the sub-theme of energy benefits, where H_a is accepted, and H_0 is rejected.